Cardiac implantable electronic device infection - how to recognize and treat? - Rochmawati, Icmi Dian; Rizal, Ardian (Heart Science Journal, 2025)
Implantable Electronic Devices (CIEDs) have significantly transformed the treatment of various heart conditions. However, their growing use has been accompanied by an increase in device-related infections, posing a serious medical concern. Early identification of CIED infections is essential for prompt and effective treatment. Typical clinical signs include localized infection symptoms—such as redness, warmth, and tenderness around the implant site—as well as general symptoms like fever and fatigue. Diagnostic support also comes from laboratory tests, particularly elevated inflammatory markers. Management of these infections requires a coordinated, multidisciplinary approach. Timely removal of the infected device is critical, along with the administration of targeted antibiotics based on culture and sensitivity findings. In some instances, surgical removal of the entire device, including any leads, may be necessary. Preventing such infections is equally important and involves strict adherence to aseptic techniques during implantation and any subsequent procedures. Prophylactic antibiotics may also be warranted for patients at high risk. In summary, the successful management of CIED infections relies on early detection, accurate diagnosis, and a well-coordinated treatment plan. Preventive measures are vital in decreasing infection rates and ensuring the best possible outcomes for patients.